The Influence of Teacher Discipline on Teacher Work Performance in the Learning Process at Rawas Ulu Muratara Vocational School, South Sumatra - Rosnida Yahya; Aman Simaremare (MASI Mandiri Edukasi, 2025)
This study investigates the influence of teacher professionalism and discipline on teacher performance at Rawas Ulu Muratara Vocational School. The core problem addressed is the variation in teacher effectiveness, which may be rooted in varying levels of professional competence and disciplinary behavior among educators. The objective of the research is to determine how significantly these two factors contribute to improving overall teacher performance and to identify the extent of their individual and combined effects. The study employed a quantitative research method grounded in a positivist paradigm, utilizing statistical analysis to examine data collected from a representative sample of teachers at the school. Instruments such as structured questionnaires were used to gather numerical data on teacher professionalism, discipline, and performance indicators. The collected data were analyzed using multiple regression techniques to measure the degree of influence each independent variable had on teacher performance. The results revealed that teacher professionalism has a dominant and significant effect, contributing 63.9% to teacher performance. Teacher discipline also significantly influences performance, with a contribution of 26.8%. When analyzed together, both professionalism and discipline account for 77.369% of the variation in teacher performance, indicating a strong combined effect. These findings highlight the urgent need for professional development and stricter enforcement of discipline policies to enhance educational outcomes. The study offers valuable insights for school leaders, policymakers, and education stakeholders seeking to implement effective strategies for improving teacher quality and overall institutional performance.